Photocatalytic Reactors. Reaction Kinetics In A Flat Plate Solar Simulator - Brandi, Rodolfo Juan (2002)
The kinetics of the photocatalytic decomposition of low concentrations of trichloroethylene (TCE) in water was modeled and the reaction parameters have been evaluated for different catalyst loadings. The employed reactor is a flat plate configuration irradiated by tubular lamps that have emission in the 300–400 nm wavelength range. The mass conservation model is two-dimensional while the developed radiation model is two-dimensional in space and two directional in radiation propagation. The performance of the photoreactor with this reaction can be properly represented employing only two lumped kinetic constants that can be derived from a 12 steps, complete reaction sequence. The deduced kinetic model has explicit functional dependencies for the local volumetric rate of photon absorption (LVRPA) and the effect of the catalyst concentration: . Values of the kinetic constants are: α=1.94×10−9 mol g1/2 cm−2 s−1/2 einstein−1/2 and α3=5.52×106 cm3 mol−1. As derived from the reaction sequence and validated with experiments, it was observed that the reaction rate is proportional to the square root of the LVRPA. The dependence on the catalyst loading, well described by the model, is more complex due to its characteristic effect on the light distribution inside the reaction space.